Three-dimensional printing in modern orthopedic trauma surgery: a comprehensive analysis of technical evolution and clinical translation - Ting Long; Linyun Tan; Linyun Tan; Xiaoyan Liu (Frontiers in Medicine, 2025)
Three-dimensional (3D) printing has emerged as a transformative technology in orthopedic trauma surgery, offering unprecedented possibilities for personalized surgical solutions. Despite its increasing adoption, there remains a lack of comprehensive reviews systematically evaluating its technical considerations and evidence-based outcomes across different anatomical regions. Through systematic review of literature from major databases and analysis of clinical evidence, this comprehensive review examines the current state of advanced 3D printing technologies in orthopedic trauma. We analyze four major additive manufacturing methodologies: vat photopolymerization for surgical guides, material extrusion for anatomical models, powder bed fusion for implants, and emerging bioprinting approaches. The integration of these technologies has substantially improved surgical outcomes through three primary approaches: preoperative planning with anatomical modeling, intraoperative guidance using custom surgical guides, and patient-specific implant solutions. Systematic analysis demonstrates significant improvements in surgical precision, operative efficiency, and anatomical restoration across various fracture patterns. While challenges in manufacturing protocols, quality control standards, and regulatory frameworks persist, ongoing innovations in materials science, digital workflow optimization, and clinical validation continue to expand the applications. This review provides a systematic framework integrating technical principles and clinical applications of 3D printing in orthopedic trauma surgery, offering practical guidelines while highlighting future research directions.